Collective struggles – collective learning: A history of women garment workers and adult education - Kenneth C. Wolensky (Adult Education Research Conference, 1996)
Since early in the 20th century workers’ education has been a vital part of the agenda of the International Ladies’ Garment Workers’ Union (ILGWU). This paper provides an overview of various aspects and examples of workers’ education in the ILGWU primarily during the first half of the 20th century. It also argues that, although the historiography of North American adult education tends to marginalize workers’ education, the efforts of the ILGWU are indeed contributory to the broader history of the field.